(3GddaX GdQGFb hGdeYfi GdaGFb aj GdMbGFb hGdWQGFbs ((3eMeO Hf eMeO Hf YHO GdQMje GdNWjH s)
(3ChdgG (B:s
(3hHYO eG RGdJ bQGFM GdCacGQ JbJVH Yhf GdeYGfi hJbJVi GdCHcGQ s
(3BNQgG (B:s
(3hYf SGFQ GdeSdejf hGdeSdeGJ hGdeDefjf hGdeDefGJMSHfG Gddg hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs